Sharḥ al-Taʿarruf li-madhhab al-taṣawwuf - al-Kalābādhī, Abū Bakr b. Isḥāq, (Miras Maktoob, ISBN: 9789004365452., 2019)
The Kitāb al-taʿarruf li-madhhab al-taṣawwuf by Abū Bakr b. Isḥāq al-Kalābādhī (d. 380-85/990-995) is one of the most famous early manuals on Sufism. Written in Bukhara under the strongly orthodox Samanids, it consists of four parts: an explanation of the term ṣūfī and a listing of famous Sufis with a typology of their writings, an exposition of the Sufī creed and its conformity with orthodox Islam, an explanation of the spiritual path of the Sufi with accompanying terminology, and a description of Sufi conduct and of their special relation with God. The work saw four commentaries, the present one by Ismāʿīl Mustamlī Būkhārī (d. 434/1043) being one of them. Starting each time with a brief quotation from the original Arabic, the commentary in Persian. This is a facsimile edition of a manuscript from the Bhīravī collection in the National Archives of Pakistan, dated 473/1081. The manuscript is incomplete, with about half of the commentary missing.